Shifting the Paradigm of the Indonesian Judicial System from The Influence of the Anglo-Saxon Judicial System - Fence M Wantu (Jambura Law Review, 2023)
The litigation process in court will run well if all the elements are carried out following their duties and functions. In addition, what is very important is the judicial system that applies. The objectives of this research are 1). To find out and analyze the paradigm of how judges think in the Indonesian justice system, which adheres to the Continental European justice system. 2). To find out and analyze the development of the Indonesian justice system, especially how judges think, which is currently influenced by the Anglo-Saxon system. This research method is normative, namely legal research that aims to find rules or norms. This research is also called library research. Results of discussion 1). that the paradigm of the way of thinking of judges in the Indonesian justice system, which adheres to the Continental European justice system, is more inclined to use statutory regulations as the basis for deciding cases. The principle adopted is the persuasive force precedent. 2). The development of the Indonesian justice system, especially the way of thinking of judges, is currently experiencing a shift, namely that it is no longer pure with the Continental European justice system but is starting to introduce what is the practice in the Anglo-Saxon justice system, for example, the practice of class action lawsuits which have been regulated in environmental laws.